Pokuta w dokumentach synodalnych chrześcijańskiej starożytności - Chłopowiec, Michał (Vox Patrum, 2010)
Theology of penance, the deed, was shaped by theologians and legislation, which mainly, in the first epoch, led to punishment. The nature of foreseen reward was (relatively) exactly defined by the quantity and quality. Obligatory resolutions where defined to current law and community, therefore undertaken resolutions were not necessarily in the scope of defined requirements, that is why, in general, rarely obligated the church. Resolutions of two synods taken place in Elwir and Ancyr, introduced in the first part of the article, deemed to have the most severe requirements, without references from synods from other provinces. The second part of the article shows decisions, undertaken by synods in concrete uses, in chosen fields of life and individual states. Over the centuries, formulated sanctions, as an example, showed a progressive appeasement of penitential achievement, even if such process was not at a uniform rate.